Perbandingan Pengaruh Persepsi Terdahap Minat Masyarakat untuk Mengunjungi Destinasi Pariwisata Halal pada Lima Kabupaten/Kota di Provinsi Daerah Istimewa Yogyakarta - Muhammad Al Faridho Awwal; Dewi Wahyu Setyo Rini (JURNAL MASTER PARIWISATA, 2019)
This study aims to examine the effect of perception on tourists’ interest in halal travel in each district / city in the Special Region of Yogyakarta. There are five districts / cities tested and compared. This study uses primary data by distributing questionnaires. In this study the results of testing using the Struqtural Equation Modeling (SEM) method and processed through the Smart PLS application software v. 3 shows that people's perception of halal tourism influences their interest in halal travel. However, in Bantul and Gunung Kidul districts the concept of perception variable does not affect the perception of development while in Yogyakarta the development perception variable does not affect the attitude of halal tourism. Nevertheless, in general community perceptions of both the concept and development affect tourists’ attitudes and affect tourists’ interest in visiting halal tourism.Keywords: persepsi, minat, pariwisata halal